Effect of Cilembu Sweet Potato Starch and Storage Times on Physicochemical and Microbiology of Synbiotic Yoghurt Ice Cream - Dewi, Lestari Kusumah; Radiati, Lilik Eka; Thohari, Imam (Graduate School, Universitas Brawijaya, 2015)
The purpose of this research was to determine the effect of adding cilembu sweet potato starch (1-6 %) and storage time (2, 4, 6 weeks) on physicochemical and microbiology of synbiotic yoghurt ice cream. The research methodology used was experiment laboratory. The first experiment was designed by Completely Randomized Design (CRD) using 7 treatments and 4 replications, while second step was designed by CRD using 4 treatments and 4 replications. Data were analized by Analysis of Variance (ANOVA) and continued by Duncan's Multiple Range Test (DMRT). Determination of the best treatment used Effectiveness Index, which has been modified. The result of first step showed the best treatment is the addition of cilembu sweet potato starch 3% with value 5.400 log10 cfu.mL-1 of total LAB, 4.322 of pH, 0.200 g.L-1 of EPS, 40.257 P of viscosity, 35.523 minutes.50g-1 of melting rate, 30.258% of overrun. For second step, the best treatment is 6 weeks stored with value 5.004 log10cfu.mL-1 of total LAB, 4.347 of pH, 0.327 g.L-1 of EPS, 114.928 P of viscosity, 48.828 minutes.50g-1 of melting rate. Keywords: cilembu sweet potato,exopolysaccharides, ice cream, periods